2016
DOI: 10.1073/pnas.1523951113
|View full text |Cite
|
Sign up to set email alerts
|

Early farmers from across Europe directly descended from Neolithic Aegeans

Abstract: Farming and sedentism first appeared in southwestern Asia during the early Holocene and later spread to neighboring regions, including Europe, along multiple dispersal routes. Conspicuous uncertainties remain about the relative roles of migration, cultural diffusion, and admixture with local foragers in the early Neolithization of Europe. Here we present paleogenomic data for five Neolithic individuals from northern Greece and northwestern Turkey spanning the time and region of the earliest spread of farming i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
271
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 408 publications
(314 citation statements)
references
References 44 publications
15
271
0
2
Order By: Relevance
“…The ancient set includes 211 Beaker Complex individuals (195 newly reported, 7 with shotgun data 3 for which we generated 1240k capture data and 9 previously published 3,4 ), 68 newly reported individuals from relevant ancient populations and 298 previously published 12,18,19,2123,5057 individuals (Supplementary Table 1). We kept 591,642 autosomal SNPs after intersecting autosomal SNPs in the 1240k capture with the analysis set of 594,924 SNPs from Lazaridis et al 11 .…”
Section: Methodsmentioning
confidence: 99%
“…The ancient set includes 211 Beaker Complex individuals (195 newly reported, 7 with shotgun data 3 for which we generated 1240k capture data and 9 previously published 3,4 ), 68 newly reported individuals from relevant ancient populations and 298 previously published 12,18,19,2123,5057 individuals (Supplementary Table 1). We kept 591,642 autosomal SNPs after intersecting autosomal SNPs in the 1240k capture with the analysis set of 594,924 SNPs from Lazaridis et al 11 .…”
Section: Methodsmentioning
confidence: 99%
“…This approach differs from the mixture model procedure described in 3,5,[32][33][34] in that it assumes that ݈ is multinomial distributed and solves for ߚ using a Bayesian approach rather than a nonnegative least squares optimization. The model is similar to the one described in 35 , but introduces new improvements in the way that λ is estimated and in the MCMC proposal procedure.…”
Section: Repeat This For 4 Additional Randomly Sampled (With Replacemmentioning
confidence: 99%
“…After the first appearance of agriculture in the mid-7 th millennium BCE 1,2 farming spread westward via a Mediterranean and northwestward via a Danubian route, and was established in both Iberia and Central Europe by 5600 BCE. 3,4 Ancient DNA studies have shown that the spread of farming across Europe was accompanied by a massive movement of people 58 closely related to the farmers of northwestern Anatolia 911 but nearly all the ancient DNA from Europe’s first farmers is from central and western Europe, with only three individuals reported from the southeast. 9 In the millennia following the establishment of agriculture in the Balkan Peninsula, a series of complex societies formed, culminating in sites such as the mid-5 th millennium BCE necropolis at Varna, which has some of the earliest evidence of extreme inequality in wealth, with one individual (grave 43) from whom we extracted DNA buried with more gold than is known from any earlier site.…”
Section: Introductionmentioning
confidence: 99%